The usability and feasibility of dailycalm application in reducing stress among adolescents during COVID-19 pandemic - Noor Azimah Muhammad; Reiko W; Muhammad Aziq A; Nurfitri Izzati ZF; Nur Afifah AM; Kuganeswari A; Nurfazidah E; Abrahman RM; Hizlinda Tohid (Pusat Perubatan Universiti Kebangsaan Malaysia, 2021)
Stress is common among adolescents that impairs their well-being. This study aimed at determining the usability and feasibility of a newly developed mobile apps, DailyCalm in reducing stress among secondary school students in Kedah. They were recruited via convenience sampling using social media in August 2020 during COVID-19 pandemic. An access link was provided to download the DailyCalm apps that contained videos teaching on breathing and relaxation techniques. Students were encouraged to use the apps thrice a week. Students responded to an online form that measured stress level using Perceived Stress Scale (PSS) at baseline and four weeks later and perception on the usability and feasibility of the apps after four weeks of use. Among the 80 students aged 13 to 17 years who completed the study, 83.8% of them were having moderate to high level of stress. The students rated the apps as moderately usable with mean of 39.91 (SD = 6.12) and highly feasible with mean of 41.74 (SD = 6.99). However, there was no significant reduction in PSS score after 4 weeks of use [mean of 18.10 (SD =5.15) at baseline and mean of 17.44 (SD =5.06) at post-intervention; p-value = 0.19]. In conclusion, DailyCalm was viewed as moderately usable and highly feasible, yet its use over 4 weeks did not show a significant reduction in the stress level experienced by the students. The DailyCalm app has the potential to be used as a stress management application but needs further improvement for an effective use.